The Role of High-Performance Work Systems in Enhancing Work Engagement - Al-Qatawneh, Manar; Abutayeh, Bandar (International Review of Management and Marketing, 2026)
Scholars and practitioners endeavor to understand the factors influencing work engagement, thereby enabling employees to display high levels of discretionary behavior, enthusiasm, and absorption in their roles within an organization. This study attempts to fill this research gap by investigating the various effects of High-Performance Work Systems (HPWS) dimensions on work engagement and its dimensions. Using a sample of 237 employees from seven commercial banks in Jordan, the study employs a quantitative research approach, including regression analysis, to investigate the proposed relationships among constructs. The results reveal that the four dimensions of High-Performance Work Systems have various effects on work engagement. The findings indicate that communication and involvement, and career management affect vigor, while performance management and rewards, and training and development influence dedication and absorption. These findings will help managers effectively allocate their rare and valuable financial and human resources to deal with work engagement issues in commercial banks.